Metode Spatial Autoregressive dalam Analisis Kerawanan Demam Berdarah Dengue di Kota Gorontalo - Mahading, Tria Susilowati; Resmawan, Resmawan; Yahya, Lailany; Akolo, Ingka Rizkiyani (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study was aimed at discussing spatial regression to find out factors influencing the dengue fever vulnerability in Gorontalo city. The spatial regression method used in this study was the Spatial Autoregressive Model (SAR). The SAR model can provide additional information about the effect of the location of the village/village on the incidence of DBD in Gorontalo City. This study concluded that the number of population, number of poor population, educational facilities and the area elevation were factors influencing the dengue fever vulnerability in the city of Gorontalo.